Statistical processing of long-term observations of groundwaters - Kriz, H (Journal of hydrology (Amsterdam), 1972)
In processing the results of long-term observations of groundwaters certain special methods are employed in Czechoslovakia. In essence, a modification of the conventional methods of mathematical statistics to the needs of groundwater hydrology is involved. The subject of this contribution is the statistical processing of seventy years' (1901–1970) observation of the weekly groundwater levels in one of the observation wells in the Bohemian Cretaceous Plateau.